Investments : analysis and behavior - Hirschey, Mark (McGraw-Hill Irwin, 2008)
This book provides students with knowledge of investment analytical tools and an understanding of the forces that drive the industry. Including Market efficiency and investor behavior, market anomalies and financial statement analysis